The (short-term) individual welfare consequences of an alcohol ban - René Petilliot (Albert-Ludwigs-Universität Freiburg, Forschungszentrum Generationenverträge (FZG), 2018)
This paper provides the first empirical analysis of the (short-term) welfare consequences of an alcohol ban. Using subjective well-being data to proxy individual welfare, I apply a regression discontinuity design where the date of the implementation of the ban in the German federal state of Baden-Wuerttemberg functions as discontinuity. I find that the ban reduces life satisfaction of the total population and the subpopulation of drinkers, while life satisfaction of nondrinkers is unaffected. My findings are well in line with the rational addiction model perspective.
Keywords: D04; D60; H30; I31; 330; Alcohol ban; Well-being; Life satisfaction; Welfare; Addiction; Regression discontinuity design